TINJAUAN HUKUM EKONOMI ISLAM TERHADAP KEDUDUKAN JAMINAN KEBENDAAN DALAM TRANSAKSI PERBANKAN SYARIAH - Ahmad Fathorrozi (CENDEKIA: Jurnal Studi Keislaman, 2022)
This article is the result of a qualitative research that aims to identified how Islamic economic law reviews the position of material security in Islamic banking transactions. Based on the results of this study, it can be concluded that the existence of sharia guarantees and the rule of law, especially in daily economic and business activities is an absolute requirement (condition sine qua non). The legal principles of sharia guarantees will serve as ethical guidelines, foundations, and guidelines as well as touchstones for validating the rule of law regarding sharia guarantees. The position of material guarantees in Islamic banking transactions is a benchmark to determine the ability of customers to fulfill their obligations, but it is only allowed so that there is no negligence in the responsibilities that exist with the customer so that from this it can create a trust between the customer and the bank.